Traumatic Orbital Compartment Syndrome: A Sight Threatening Emergency - Singh, Kinsuk; Shrestha, Gulshan Bahadur (Nepalese Journal of Ophthalmology, 2019)
Orbital compartment syndrome is a rare presentation of orbital trauma and is an ophthalmic emergency. Delay in clinical diagnosis and subsequent surgical intervention will lead to loss of vision in nick of time. We presented a case series of orbital compartment syndrome secondary to trauma who presented to the emergency department of Tribhuvan University Teaching Hospital during the devastating earthquake in April 2015. Clinical diagnosis of orbital compartment syndrome was made in the bedside and all the patients underwent emergency lateral canthotomy and inferior cantholysis. This case series was aimed to describe clinical features and management of orbital compartment syndrome.